Mercury and methyl mercury in fishes from Bacajá River (Brazilian Amazon): evidence for bioaccumulation and biomagnification. Issue 1 (31st May 2016) - Souza‐Araujo, J.; Giarrizzo, T.; Lima, M. O.; Souza, M. B. G.
Abstract : This study assessed total mercury (THg) and methyl mercury (MeHg) concentrations, bioaccumulation and biomagnification of THg through the food web in fishes consumed by indigenous communities of Bacajá River, the largest tributary of the right bank of Xingu River. In total, 496 fish (22 species) were sampled. Nine species had THg concentrations above the limit recommended by the World Health Organisation (0·5 µg g −1 wet mass), and one exceeded the recommended level for Hg in predatory fishes by Brazilian law (1·0 µg g −1 ). The average concentration of THg increased significantly with trophic guild (herbivorous to piscivorous) and trophic level, with higher accumulation in fishes with greater total length. Ninety‐six per cent of all mercury was methylated. These results suggest that feeding habits determine THg concentrations in fishes and that Hg elimination rate is slow during growth, which allows greater accumulation. These findings show that fishes in the Bacajá River contain high concentrations of THg and MeHg.